La responsabilidad social universitaria desde el derecho administrativo - Villegas Vega, Paul (2021)
In this article, the authors seek to make administrative law visible as a tool for university social responsibility. For this purpose, a qualitative methodology is used, which involves the review of norms and specialized doctrine that allows, on the one hand, the identification of the actors responsible for the fulfillment of public purposes and/or interests such as the State and the university; and, on the other hand, the development of the university social responsibility approach in Peru and the systematization of activities carried out in the framework of the implementation of the university social responsibility initiative promoted by the Pontificia Universidad Católica del Peru, in collaboration with the Municipality of Miraflores in Lima, Peru.